2012
DOI: 10.1016/j.physleta.2012.04.058
|View full text |Cite
|
Sign up to set email alerts
|

A class of solvable coupled nonlinear oscillators with amplitude independent frequencies

Abstract: Existence of amplitude independent frequencies of oscillation is an unusual property for a nonlinear oscillator. We find that a class of N coupled nonlinear Liénard type oscillators exhibit this interesting property. We show that a specific subset can be explicitly solved from which we demonstrate the existence of periodic and quasiperiodic solutions. Another set of N-coupled nonlinear oscillators, possessing the amplitude independent nature of frequencies, is almost integrable in the sense that the system can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Since then Liénard equations have been applied to many different areas even in biology [19]. The particular Liénard equation (5) has been extensively studied by many authors, the most recent papers being [20][21][22][23]. In [24][25][26] Lie group analysis was applied to (6) and it was shown that equation (5) is the only linearizable equation among those in (6).…”
Section: Classical Properties Of the Liénard Equation (5)mentioning
confidence: 99%
“…Since then Liénard equations have been applied to many different areas even in biology [19]. The particular Liénard equation (5) has been extensively studied by many authors, the most recent papers being [20][21][22][23]. In [24][25][26] Lie group analysis was applied to (6) and it was shown that equation (5) is the only linearizable equation among those in (6).…”
Section: Classical Properties Of the Liénard Equation (5)mentioning
confidence: 99%
“…[8][9][10][11] The mathematical properties of LT equations in its general form have been intensively exercised, and their study remains an active field of research in applied sciences and engineering. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Recently, in a series of work, Harko and his collaborators studied various aspects of GL and LT equations in different forms. [8][9][10][11] In their works, they tried to establish the integrability conditions of a variety of GL/LT equations through their reduction to first-order equations of Riccati or Abel type.…”
Section: Introductionmentioning
confidence: 99%
“…In [24] the same quantization scheme was applied in order to quantize the second-order Riccati equation while in [25] the quantization of Calogero's goldfish system was achieved. In [11] it was shown that this method straightforwardly yields the Schrödinger equation in the momentum space of a Liénard-type nonlinear oscillator as given in [4].…”
Section: Introductionmentioning
confidence: 99%